Adābur Rihlāt lī Karl Ṭambsūn fī Kitāb Jaulah fī Rub’I Āsiyā lī Muhammad Tsābit - Siti Nur Suci Maulidia; Moh Zawawi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
Jaulah fi Rubu'I Asia is a travelogue that presents Muhammad Tsabit's journey to a quarter of the Asian continent. His travel notes describe the culture, wonders, and uniqueness found in the countries he visited. The purpose of this study is to analyze the depiction of the world, especially in India, in the book Jaualah fi Rubu'I Asia which written in Arabic, reveal the author's subjectivity to what he experienced during the trip, and reveal the culture of the author and the culture of the area visited and find out the author's reaction or response to the new locations he encountered. The researcher uses Carl Thompson's travel writing theory to study it, which has three basic concepts: reporting the world, revealing the self, and representing the other. The research method used is descriptive qualitative. The data in this study are in the form of quotations of phrases, clauses, or sentences in the book Jualah fi Rubu'I Asia. The data collection technique uses the read-write technique. At the same time, the data analysis technique uses the Miles & Huberman analysis model. The result of this research is that the world reported by the author is expressed through the depiction of culture in various aspects. In describing the culture, the author gives his subjectivity through the assumptions and feelings he expresses. Therefore, the author is classified as a romantic traveler. The author uses a colonial discourse strategy in his writing, where the other is both the inferior and superior party.